Aggressive natural killer cell leukemia or extranodal NK/T cell lymphoma? a case with nasal involvement - Xiaoke Jin; Youhai Xu; Jun Zhang; Guangxi Li; Dongping Huang; Yuqiong Yang; Hesheng He (BMC, 2017)
Abstract Background Aggressive natural killer cell leukemia/lymphoma (ANKL) is a rare and highly aggressive NK cell neoplasm with a short clinical course and poor prognosis and is often misdiagnosed and confused with NK/T cell lymphoma (NKTL), which has a very different prognosis. Here, we present a case with nasal and bone marrow involvement, provide a literature review and make a differential diagnosis. Case presentation A 41-year-old male presented nasal congestion pharyngalgia, palatal perforation, high fever and multiorgan dysfunction. Our diagnosis primarily relied on clinical features, the morphology and immunophenotype of the neoplastic cells and imaging studies. Characteristic large granular lymphocytes with azurophilic granules were visible in the bone marrow smears. In addition, the neoplastic cells expressed a typical immunophenotype, and the T cell receptor γ (TCR-γ) gene rearrangement analysis and presence of Epstein-Barr virus (EBV) were negative. The patient's symptoms and signs were temporarily relieved after chemotherapy treatment, but after a short time, he underwent a rapid clinical decline and died 8 weeks later after admission due to multiorgan function failure. Conclusion Our case demonstrates that to avoid a misdiagnosis, bone marrow analyses and other examinations should be performed early when a patient initially presents nasal lesions and other systemic symptoms. To the best of our knowledge, this may be the first reported case of ANKL with sternal tenderness.